Diagnostic Accuracy of Recto-Sigmoid Index Evaluation on Barium Enema in Hirchsprung’s Disease - Emma Ratna Fury1 , Andy Darma2 , Alpha Fardah Athiyyah3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Hirschsprung’s disease is a congenital disease caused by the absence of ganglion cellsin the bowel wall, which results in functional obstruction of the aganglionic segment due to failure ofrelaxation during peristalsis. The recto-sigmoid index on barium enema may constitute in the diagnosis ofHirschsprung’s disease.Aim: To evaluate the sensitivity, specificity, positive predictive value, and negative predictive value ofrecto-sigmoid index for the diagnosis of Hirschsprung’s disease in patients who underwent barium enemaexamination.Methods: This retrospective study was conducted in Dr Soetomo Hospital. Medical records of patientssuspected of Hirscsprung’s disease who underwent both barium enema examination and diagnostic fullthickness biopsy were evaluated. Moreover, the sensitivity, specificity, positive predictive value (PPV), andnegative predictive value (NPV) of recto-sigmoid index was calculated.Results: A total of 37 patients were examined; 21 of them were male. The average age was 24.5 (SD 17.34,range 1 month-72 month). Biopsy revealed the absence of ganglion cells in 32 (91,8%) patients. The rectosigmoid index agreed with the histopathologic diagnosis in 30 (81%.) patients. The sensitivity, specificity,PPV, and NPV were 87.5%, 40%, 90.5% and 33% respectively.Conclusion: Recto-sigmoid index evaluation in barium enema for the diagnosis of Hirscsprung’s diseasehas poor diagnostic accuracy.